A influência atual da Igreja Católica Apostólica Romana no direito brasileiro: caso do julgamento da constitucionalidade do artigo 5º da lei de biossegurança - Ramiro, Marcus Geandré Nakano (2010)
The present work studies the current influence of the Roman Catholic Apostolic Church on Brazilian law in the specific case of the trial on the constitutionality of article 5 of the Biosecurity Law (Law nº. 11,105/2005). To that end, it discusses the importance of social groups in forming the Law, the relationships in the scope of religion and international law between the Catholic Church and the Brazilian State, and the result of the trial on the Direct Action of Unconstitutionality through the study of the full votes by the justices of the Federal Supreme Court